RELATIONSHIPS FOR GRAMATICAL COMPETENCY AND ATTITUDES TOWARDS INDONESIAN LANGUAGE WITH ARGUMENTATION WRITING SKILLS - Lili Dismiana; Turdjai Turdjai (UNIB Press, 2019)
This study aims to: 1) Describe the relationship between grammatical competence and argumentation writing skills. 2) Describe the relationship between attitude towards Indonesian and argumentation writing skills. 3) Describe the relationship between grammatical competence and attitude towards Indonesian language together with argument writing skills in class XII MAN 1 Lahat.This type of research is a correlation study with a population of 287 people and a sample of 140 people. The method in this study is an experimental method by providing tests and questionnaires. Data analysis techniques used are descriptive statistical techniques (deductive data analysis) and inferential (inductive data analysis).This research concludes: 1) there is a significant relationship between grammatical competence with argumentation writing skills in class XII MAN 1 Lahat. 2) there is a significant relationship between attitude towards Indonesian language with argumentation writing skills in class XII MAN 1 Lahat. 3) there is a significant relationship between grammatical competence with attitudes toward language together with argument writing skills in class XII MAN 1 Lahat